2009
DOI: 10.1161/hypertensionaha.108.120816
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of Receptor-Associated Late Transducer Inhibits Maladaptive Hypertrophy via Blocking Epidermal Growth Factor Receptor Signaling

Abstract: Abstract-Receptor-associated late transducer (RALT) is a feedback inhibitor of epidermal growth factor receptor signaling. RALT has been shown previously to be induced in the ischemic heart and to promote cardiomyocyte apoptosis in vitro. However, the role of RALT in cardiac hypertrophy remains unclear. We hypothesized that forced expression of RALT in the murine heart would protect the heart against cardiac hypertrophy in vivo. We investigated the effect of cardiac overexpression of rat RALT on cardiac hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 29 publications
1
18
0
1
Order By: Relevance
“…In an attempt to elucidate the mechanisms underlying the inhibitory effect of Rgs5 on fibrosis, we analyzed key components of TGF-β1/Smad signal transduction. Blockade of this signaling pathway was predicted to blunt fibrosis (19). In line with these notions, our data suggest that Rgs5 abrogates Smad 2 phosphorylation and Smad 2/3 translocation in both cultured cardiac fibroblasts and hypertrophied hearts, thus inhibiting collagen synthesis and fibrosis.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In an attempt to elucidate the mechanisms underlying the inhibitory effect of Rgs5 on fibrosis, we analyzed key components of TGF-β1/Smad signal transduction. Blockade of this signaling pathway was predicted to blunt fibrosis (19). In line with these notions, our data suggest that Rgs5 abrogates Smad 2 phosphorylation and Smad 2/3 translocation in both cultured cardiac fibroblasts and hypertrophied hearts, thus inhibiting collagen synthesis and fibrosis.…”
Section: Discussionsupporting
confidence: 82%
“…Protein and collagen synthesis were assessed by [ 3 H]-leucine and [ 3 H]-proline incorporation as described previously (19,20). For the surface areas, the cells were fixed with 3.7% formaldehyde in PBS solution, permeabilized in 0.1% Triton X-100 in PBS solution, and stained with α-actinin (Sigma) at a dilution of 1:100 by standard immunocytochemical techniques.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies with antisense infusion demonstrated suppression of left ventricular hypertrophy in SHR and in rats with AngII infusion (49; 50). In addition, transgenic mice overexpressing receptor-associated late transducer, a feedback inhibitor of EGFR signaling, do not develop AngII-induced cardiac hypertrophy (98). As shown in culture, cardiac hypertrophy is attenuated with an ADAM inhibitor in mice with AngII infusion (90).…”
Section: Heartmentioning
confidence: 99%
“…1,2 Although initially a beneficial adaptive response, prolonged hypertrophy may result in ventricular dilatation and heart failure, which is increasing in prevalence and is a debilitating disease with high rates of mortality and morbidity. [3][4][5][6] However, antihypertensive therapies and aortic valve replacement are the only 2 treatments proven to effectively reverse both structural and functional cardiac abnormalities associated with pathological cardiac hypertrophy. Understanding the underlying processes regulating cardiac remodeling will allow us to identify specific new therapies to improve the long-term outcomes of pathological cardiac hypertrophy in patients.…”
mentioning
confidence: 99%